The abundance of phytoplankton and its relationship to the N/P ratio in Jakarta Bay, Indonesia - TUMPAK SIDABUTAR; DIETRIECH G. BENGEN; SAM WOUTHUYZEN; TRI PARTONO (Society for Indonesian Biodiversity, 2016)
Sidabutar T, Bengen DG, Wouthuyzen S, Partono T. 2016. The abundance of phytoplankton and its relationship to the N/P ratio in Jakarta Bay, Indonesia. Biodiversitas 17: 673-678. The occurrence of phytoplankton blooms in Jakarta Bay has increased significantly, and resulted in, the mass mortality of fish and other organisms. Phytoplankton bloom events are indicated by a change in the color of the sea’s surface. Generally, phytoplankton growth is influenced by the levels of nutrients in the water, while spatial distribution is influenced by the pattern of the current. In connection with this phenomenon, research was conducted in 2010, 2011 and 2013, to determine the abundance and distribution of phytoplankton and their connection with the N/P ratio. The results showed that the abundance of phytoplankton ranged from 40x106 cells/m3 up to 1699.1x106 cells/m3, with the highest recorded data was during the east monsoon in 2010 and the lowest during the first transition period of 2011. The predominant phytoplanktons were frequently diatoms such as Skeletonema, Chaetoceros and Thalassiosira. The distribution of phytoplankton seemingly follows the nutrient concentration ratio where phosphate acted as the limiting factor and nitrogen as the triggering factor. The higher the N/P ratio, the more potentially uncontrolled growth of phytoplankton occurred. When the availability of nutrients increased an increase in total algal biomass occurred, however, the alteration in nutrient composition led to a change in composition of community.